RELAÇÕES DE SUPORTE E BEM-ESTAR NO TRABALHO EM PESSOAS COM DEFICIÊNCIA - Pereira, Ursula de Souza Barboza (2009)
Since ancient times, it s conspicuous humanity s quest to understand and conquer happiness, quality of life, well-being and health in their bio-psycho-social fulfillment. Thus, the general goal of this study was to analyze the relations between support perceptions (social, social at work and organizational) and well-being at work (satisfaction at work, engagement with work and affective organizational commitment) in workers with disabilities, for few are the researches into people with disabilities (PWD). The purpose of approaching such work is for its being an important element of social integration and for constituting a symbol of social recognition, valuing the capacity of narrowing contacts and establishing social relations. 44 workers with some kind of disability and who work in operational, technical and administrative positions took part in this study. They were all chosen for convenience, being 24 (54.5%) male and 20 (45.5%) female, aged between 18 and 65. It was possible to classify the participants disabilities into four categories: upper limbs disability: 9 (20.5%) workers; lower limbs disability: 11 (25%) workers; auditory disability: 21 (47.7%) workers; visual disability: 3 (6.8%) workers. For the data collection a self-filling questionnaire was used, composed of six scales which evaluate satisfaction at work, engagement with work and organizational commitment, besides social and organizational supports. Descriptive statistical analyses were carried out, differences among averages were tested, as well as correlation coefficients among variables were calculated. The results point out that in terms of satisfaction at work, there is no sign of discrepancies between studies conducted with workers without disabilities (considered normal ). It was also possible to observe that the PWD state to be proud of the company they work for, besides being glad, enthusiastic, interested and encouraged with the employing organization. The study revealed that the PWD obtain emotional help from their social network that provide them with supportive feeling in front of difficulties or affective needs, since they are likely to understand they can count on this network to celebrate achievements and success, as they can receive care and comfort whenever they get frustrated or go through any sad moment likewise. It is possible to affirm that the PWD realize that this same network would be able to provide them with some kind of practical support, as receiving information regarding their health, maybe rehabilitation, also information for professional update or even follow-up on their development, inclusively search for new opportunities and challenges towards personal and professional growth. The results of this research show that the PWD tend to maintain a strong conviction that the company they work in worries about their well-being and is willing to offer help in front of a necessity. Further results signal that the PWD tend to increase their ties with work experiencing more satisfaction as the supports offered by the organization, by the social network both inside and outside the work context also increase. The analysis of all the content is the great contribution of this study, for being regarded as pioneering in this discussion, but future studies can confirm such results and corroborate with further information.(AU)